Case Report: CD19 CAR-T therapy induces durable remission in a pediatric patient with TP53-mutated, refractory Burkitt lymphoma: a 30-month follow-up - Zhou, Yong; Shen, Xuerong; Chen, Qinwei; Guo, Yuping; Shen, Dongyan; Su, Rui (Frontiers in Oncology, 2026)
Burkitt lymphoma (BL) with TP53 mutations is characterized by strong chemoresistance and poor prognosis, posing significant challenges in clinical treatment. Chimeric antigen receptor T-cell (CAR-T) therapy has shown promise in refractory/relapsed (r/r) BL, but its efficacy in TP53-mutated cases remains to be further validated. This case report describes a 16-year-old male adolescent diagnosed with TP53-mutated BL, whose initial presentation with recurrent abdominal pain led to a misdiagnosis of high-grade B-cell lymphoma. The disease was refractory to two cycles of chemotherapy (DA-EPOCH-R and AZA + R-CDOP) and even progression after third-line R-CODOX-M therapy. Following reevaluation confirming BL, the patient received CD19-directed CAR-T cell therapy (Axicabtagene Ciloleucel infusion, Axi-cel) and achieved complete metabolic response (CMR). Baseline lactate dehydrogenase (LDH) was markedly elevated at 1,343 U/L. As of the latest follow-up in March 2025, the patient remains in remission at 30 months after CAR-T infusion with full functional recovery, including resumption of normal academic life. This case, among the youngest reported uses of commercial Axi-cel for BL, highlights the diagnostic complexity in adolescent lymphoma and demonstrates that CD19 CAR-T therapy can overcome TP53-associated chemoresistance in adolescent BL. It also suggests that integrating molecular profiling and immunotherapy may provide new strategies for managing high-risk, treatment-refractory cases in the adolescent and young adult population.